Improving the cognitive functions in the middle-aged patients with essential arterial hypertension after the treatment with amlodipine/valsartan single-pill combination - O. D. Ostroumova; E. V. Borisova; A. I. Kochetkov; T. M. Ostroumova; O. V. Bondarec (Рациональная фармакотерапия в кардиологии)
Different antihypertensive drugs differently affect cognitive function, and data on the effect of single-pill combination (SPC) of antihypertensive drugs on cognitive function are presented only in single studies.Aim. To investigate the impact of amlodipine/valsartan SPC (A/V SPC) on blood pressure (BP) level and cognitive functions in the middle-aged antihypertensive treatment-naive patients with stage II grade 1-2 essential arterial hypertension.Methods. A group of patients with stage II grade 1-2 essential arterial hypertension who had not previously received regular antihypertensive treatment (n=38, age 49.7±7.0 years) was retrospectively formed. All the patients were treated with A/V SPC and all of them achieved target office BP (less than 140/90 mm Hg). And after 12-week follow-up (since the time of reaching the target BP) the antihypertensive treatment efficacy assessment using ambulatory BP monitoring (ABPM) were performed in all included hypertensive patients. Age-matched healthy people with normal BP (n=20, mean age 45.4±5.1years) represented a control group. In all participants cognitive functions were evaluated by 5 different tests at baseline and at the end of follow-up: Montreal Cognitive Assessment (MoCA); Trail Making test (part A and part B), Stroop Color and Word Test; verbal fluency test; 10-item word list learning task. Baseline Hamilton depression and anxiety rating scale data were also available in all individuals.Results. According to the ABPM data 24-hour, day-time and night-time systolic, diastolic and pulse BP significantly decreased after the treatment with A/V SPC (p<0.001 for systolic and diastolic BP and p<0.01 for pulse BP). After the treatment with A/V SPC significantly improved results of cognitive tests in hypertensive patients: decreased time in Trail Making Test part B (from 114.7±37.0 to 96.3±26.5 s; р=0.001); time difference between part B and part A of Trail Making Test (from 75.2±32.8 to 57.7±20.1 s; р=0.002); time in Stroop test part 3 (from 117.0±28.1 to 108.0±28.4 s; р=0.013); and interference score (from 50.9±19.2 to 43.1±22.0 s; р=0.011); increased MoCA score (from 28.4±1.3 to 29.4±1.2; р=0.001); as well as increased the 10-item word list learning task – immediate recall (from 5.7±1.3 to 6.5±1.2 words; р=0.001); 10-item word list learning task – delayed recall (from 6.3±2.1 to 6.9±1.7 words; р=0.006); literal fluency (from 11.7±3.4 to 13.2±3.2 words; р=0.020) and categorical fluency (from 7.3±2.5 to 9.5±2.9 words; p<0.001). In control group at the end of follow-up compared to baseline significantly increased the 10-item word list learning task – immediate recall (from 5.8±0.9 to 6.6±1.1 words; р<0.05) and delayed recall (from 5.9±1.8 to 8.2±1.4 words; р<0.001).Conclusion. In retrospective analysis improvement of cognitive function was found in middle-aged patients with hypertension, taking A/V SPC for 12 weeks after reaching the target BP.